Increased monocyte count and red cell distribution width as prognostic biomarkers in patients with Idiopathic Pulmonary Fibrosis - Karampitsakos, Theodoros; Torrisi, Sebastiano Emanuele; Antoniou, Katerina; Manali, Effrosyni; Korbila, Ioanna; Papaioannou, Ourania; Sampsonas, Fotios; Katsaras, Matthaios; Vasarmidi, Eirini; Papakosta, Despoina; Domvri, Kalliopi; Fouka, Eva; et al. (Respiratory research, 2021)
Idiopathic Pulmonary Fibrosis (IPF) represents a chronic lung disease with unpredictable course.
Gesehen am 25.08.2021